Layout Redesign Analysis Plastic Tarpaper Production Floor Uses Craft Algorithm Method at PT. Limmas Anugrah Plasindo - Roesmita Sukma Alam (Universitas KH. Abdul Chalim Mojokerto, 2025)
A good layout will provide efficient material flow, shorter material movement distances, and minimal material movement costs. Several techniques can be used to rearrange an inappropriate layout. One way to rearrange the layout is to use the CRAFT (Computerized Relative Allocation of Facilities Technique) method, which is a software improvement program that aims to find the optimal design by gradually improving the layout. The CRAFT method itself has been widely used to improve and develop the effectiveness of layouts in companies and agencies and optimize land use and emphasize OMH values. PT. Limmas Anugrah Plasindo is a manufacturing company engaged in the production of rolled plastic tarpaulins that always maintains product quality. Where the machines experience backtracking (land use problems) so that the distance traveled becomes far. Therefore, this study proposes a layout to reduce the distance and cost of OMH, resulting in a reduction in OMH costs of Rp. 306,622.74 from the initial total of Rp. 1,285,628.80. and a reduction in land by 272m. The implementation of the CRAFT method still refers to field conditions and agreements from the company by also considering aspects of worker comfort, storage of finished goods and others.